MEMPERSOALKAN PROGRAM JALUR TAMAT BELAJAR TANPA SKRIPSI Pada Program Studi Ilmu Komunikasi (sebuah penelitian awal melalui studi komparatif) - Kustiatno, Kustiatno (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
Communication science Faculty  of University of Prof.  DR. Moestopo (  Beragama )  Jakarta Always commit itself to supper the government to  FulfHI one  of  the  Indonesia  Republic goal  on to mate  Indonesia people smarter which is written on vision and mission at the communication   science    of    University   of    Prof.    Dr.   Moestopo (Beragama) Jakarta That is to increase the Tri  Dharma  activity, those are to evaluate,  to  maintain  and  to supply ideas  on developing  the Communication  Science through  teaching, researching, and devotion to the society to create strong and Independent passed graduate. Furthermore,  after  Communication science  Faculty  of  University  of Prof Dr. Moestopo (  Beragama ) Jakarta got A grade according to the decision of national college Accreditation  Institution number 012/BAN- PT/AK-VII/S1Nll/2003   on  July  2003  Hence  the  quality  of  passed graduate got serious attention from the head (dean) of Communication Science faculty  and also from the  University. On the other hand the quality of the passed graduate,  experience shows that the percentageof the amount of passed graduate in has degradation.